The performance of agriculture in latin america: analysing efficiency and efficacy in the region - Nelson Guilherme Machado Pinto; Vanessa Piovesan Rossato; Daniel Arruda Coronel; Aline Beatriz Schuh (Revista Facultad de Ciencias Económicas)
The objective of this study was to analyze the performance of agricultural activities in Latin American countries based on efficiency and efficacy models using data from the decade beginning in the year 2000. We observed that, even if agricultural activity is extremely important for Latin American countries, the results show many differences for these activities as there was a different impact for each country. The regions with the highest efficiency rates are found in Uruguay, Panama, and Argentina, and those with higher efficacy values are in Argentina, Brazil, and Uruguay. The results also show that countries such as El Salvador and Paraguay need to be more thorough. Regarding the relation between the two aspects studied, it is noteworthy that efficiency positively impacts efficacy in the context of agriculture in Latin America.